2009
DOI: 10.1177/0093854809347738
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Violent Patients in an Inpatient Psychiatric Hospital

Abstract: This study examines the prevalence and the individual characteristics of chronically violent patients (CVPs) in a psychiatric hospital during inpatient treatment. The study is based on a 1-year follow-up investigation of all violent episodes committed by a sample of 527 patients in a forensic psychiatric hospital in British Columbia, Canada. Sociodemographic, legal and criminological, historical, and clinical factors were analyzed using a risk assessment scheme. Approximately 10% of the sample was responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 38 publications
4
37
0
1
Order By: Relevance
“…Finally, individuals with a history of NSSI tend to report engaging in more impulsive behaviour (Herpertz, Sass, & Favazza, 1997) and demonstrate more impulsive behaviour in laboratory tasks than individuals who do not engage in NSSI (Glenn & Klonsky, 2010 (White et al, 1999). In addition, a diagnosis of substance use disorder has been associated with chronic engagement in violence (i.e., 15 or more episodes of violence) in a psychiatric inpatient sample (Lussier et al, 2010). Similar to impulsivity, substance misuse is considered to be an important risk factor for violent behaviour (Monahan et al, 2000;Douglas & Kropp, 2002), and is included as a standalone item in a frequently used violence risk assessment guide (i.e., HCR-20; Webster et al, 1997).…”
Section: Individual Factorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, individuals with a history of NSSI tend to report engaging in more impulsive behaviour (Herpertz, Sass, & Favazza, 1997) and demonstrate more impulsive behaviour in laboratory tasks than individuals who do not engage in NSSI (Glenn & Klonsky, 2010 (White et al, 1999). In addition, a diagnosis of substance use disorder has been associated with chronic engagement in violence (i.e., 15 or more episodes of violence) in a psychiatric inpatient sample (Lussier et al, 2010). Similar to impulsivity, substance misuse is considered to be an important risk factor for violent behaviour (Monahan et al, 2000;Douglas & Kropp, 2002), and is included as a standalone item in a frequently used violence risk assessment guide (i.e., HCR-20; Webster et al, 1997).…”
Section: Individual Factorsmentioning
confidence: 97%
“…Previous research in the area of violence risk assessment has consistently noted the strong association of personality disorders with violence (Rabkin, 1979;Lussier, Verdun-Jones, Deslauriers-Varin, Nicholls, & Brink, 2010). Moreover, the presence of a personality disorder is often considered to be a risk factor for future violent behaviour (Webster et al, 1997;Douglas & Kropp, 2002).…”
Section: Individual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further examination of the sample revealed that a small subset (10 %) of the population (N ¼ 527) was responsible for 60 % of all perpetrated aggression (Lussier et al 2010). An analysis of patients who were responsible for 15 or more violent episodes, and thus had more SR incidents, revealed that they were more likely to be female, have a prior criminal record for violent crime and have been found unfit or NCR on previous occasions.…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…Additional evidence also points to a particular subset of individuals perpetrating this violence. It tends to be young males with a history of violence (El-Badri & Mellsop, 2006) and it also tends to be the same people (Lussier et al 2009). …”
Section: Introductionmentioning
confidence: 99%